How Customers and Employees of Perceptive Informatics Feel about Software as A Service Deployment Model and What Are the Barriers They Feel that Exist towards Adoption of the Model? - Panneerselvam, Arunkumar (2012)
Software-as-a-Service deployment model has become the way forward for many technology companies. Most companies with an established on-premise business are looking to adopt SaaS deployment model to incorporate SaaS offerings into their product portfolio. Gartner (2012) expects the SaaS enterprise application market to grow from $11.8 billion in 2012 to $26.5billion in 2016 generating a 17.4% compound annual growth rate.